EVALUASI STATUS UNSUR HARA MAKRO PRIMER DI DESA IBRU KECAMATAN MESTONG KABUPATEN MUARO JAMBI - Permata, Winda; Farni, Yulfita; Mastur, Agus Kurniawan; Junedi, Heri; Zuhdi, Mohd (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
Soil fertility status is a key factor in determining the sustainability and productivity of agricultural systems, especially in areas with acidic soils such as Ultisols and Inceptisols. Land management without accurate nutrient status information can lead to misapplied fertilizers, low input efficiency, and continued soil fertility decline. This study aims to evaluate the status of primary macronutrients nitrogen (N), phosphorus (P), and potassium (K) in Ibru Village, Mestong Subdistrict, Muaro Jambi Regency as a basis for developing recommendations for more appropriate and sustainable land management. The study was conducted using a soil survey method with a 350 × 350 m grid at a 1:25,000 map scale. Land units were determined by overlaying soil texture, slope gradient, and land-use maps, yielding 12 Homogeneous Land Units (SLH) representing shrubland, oil palm, and rubber plantations. Disturbed soil samples were collected at 0–30 cm depth and analyzed for soil pH, organic C, total N, total P, and total K. The results showed that most of the soils were classified as very acidic to acidic (pH 3.82–5.83), with low to high organic C content (1.08–5.18%), low to moderate total N (0.12–0.29%), generally very low total P due to fixation in acidic soil conditions, and total K ranging from very low to high. These findings emphasize the importance of survey-based soil fertility evaluation and homogeneous land units as a basis for site-specific nutrient management.